Konseling Kognitif-Behavioral-Terapi (CBT) Mengatasi Perilaku Remaja Yang Marah - Pardi, Pardi (Green Publisher Indonesia, 2024)
impacts if not properly managed. Adolescent anger is triggered by various factors such as frustration, provocation, and misunderstandings, and if uncontrolled, it can lead to aggressive behavior. Cognitive-Behavioral Therapy (CBT) is an effective therapeutic approach to help adolescents manage their anger. CBT focuses on the interaction between thoughts, emotions, and behaviors, aiming to identify and change negative thought patterns that lead to anger. Through CBT, adolescents are taught emotional regulation and social problem-solving skills, enabling them to respond to challenging situations more assertively. Research shows that applying CBT to adolescents effectively reduces aggressive behaviors and enhances anger control. Thus, CBT is proven to be an effective method in helping adolescents overcome anger issues and develop more positive behavior.